Understanding The Impact Of Social Empowerment Perception Toward Purchase Intention Of Social Enterprise Craft Products - Salma Amalia Sulthanah (Journal of International Conference Proceedings (JICP), 2019)
Social entrepreneurship is an arising trend that exists as an alternative to the economy and helps fulfilling social needs that commercial entrepreneurs can’t fulfill. The research attempted to investigate the impact of social empowerment perception toward the purchase intention of craft products from social enterprise. There is an interesting finding that shows social empowerment perception has no significant influence on purchase intention in craft products of social enterprise. Rather, the labeling that explains the social cause and how products were made has strongest influence, followed by customer’s attitude on social enterprise and ecological perception on the product. Therefore, social entrepreneurs in Indonesia may be recommended to optimize products in those three aspects in order to influence purchase intention of customers